2013
DOI: 10.1152/ajpregu.00213.2012
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor modulates vascular response in soluble epoxide hydrolase-null mice through CYP-epoxygenases and PPARγ

Abstract: Nayeem MA, Pradhan I, Mustafa SJ, Morisseau C, Falck JR, Zeldin DC. Adenosine A2A receptor modulates vascular response in soluble epoxide hydrolase-null mice through CYP-epoxygenases and PPAR␥.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(113 citation statements)
references
References 63 publications
10
103
0
Order By: Relevance
“…2a), indicating the involvement of PPARγ downstream of A 2A AR to produce enhanced vascular relaxation in mice in response to HS diet. This finding is in agreement with our previous published work [39] and others [27, 40] and confirms the contribution of PPARγ in A 2A AR-mediated vascular response.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2a), indicating the involvement of PPARγ downstream of A 2A AR to produce enhanced vascular relaxation in mice in response to HS diet. This finding is in agreement with our previous published work [39] and others [27, 40] and confirms the contribution of PPARγ in A 2A AR-mediated vascular response.…”
Section: Discussionsupporting
confidence: 94%
“…6), implicating the contribution of K ATP channel in PPARγ-mediated vascular relaxation. Taken together, these data suggest that A 2A AR-EETs-PPARγ pathway produces vascular relaxation through K ATP channel which is consistent with our earlier reports [10, 39], suggesting that PPARγ elicits relaxation in both mouse vascular and human pulmonary arteries by activating K ATP channels [31]. …”
Section: Discussionsupporting
confidence: 92%
“…Various studies revealed that a decrease in A 1 AR levels closely followed a decrease in sEH expression, and vice versa in sEH −/− and A 2A AR −/− mouse aortas [19, 21]. Additionally, sEH inhibition reduced A 1 AR-dependent aortic contractions in A 2A AR −/− mice [21].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported enhanced adenosine receptors (AR)-dependent vascular relaxation in the aorta of sEH knockout ( −/− ) mice [19]. This increase in relaxation was attributed to enhanced A 2A AR and decreased A 1 AR protein expression [19]. In A 2A AR −/− mouse aorta, we found higher expression of A 1 AR [20] and sEH [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation